2006
DOI: 10.1007/s00701-006-0847-9
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and prognosis of delayed facial palsy after microvascular decompression for hemifacial spasm

Abstract: Our findings demonstrated that the incidence of DFP was not so low as has been reported the literature, and it did not have any striking predisposing factors. Even though the degree of facial palsy was variable, almost all patients exhibited a complete recovery without any further special treatment. The etiology of DFP and its association with herpes infection should be further clarified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
41
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(48 citation statements)
references
References 11 publications
6
41
1
Order By: Relevance
“…The major postoperative complications included permanent hearing loss in 6 (1.8%), immediate facial weakness in 4 (1.4%), delayed facial weakness in 6 (2.0%), and cerebrospinal fluid leakage in 1 (0.3%). One patient with delayed facial palsy had spontaneous symptom improvement 19) . There was neither death nor ischemic insults in our series.…”
Section: Resultsmentioning
confidence: 96%
“…The major postoperative complications included permanent hearing loss in 6 (1.8%), immediate facial weakness in 4 (1.4%), delayed facial weakness in 6 (2.0%), and cerebrospinal fluid leakage in 1 (0.3%). One patient with delayed facial palsy had spontaneous symptom improvement 19) . There was neither death nor ischemic insults in our series.…”
Section: Resultsmentioning
confidence: 96%
“…In table 3, we compared the clinical results of our patients with previously reported results of DFP patients who underwent MVD for HFS. Although facial spasm completely disappeared after MVD, delayed facial weakness may decrease the patient’s individual satisfaction [1,5,7,38,39,40]. With delayed facial weakness after surgery, relevant explanations have been introduced including reactivation of HSV, delayed facial nerve edema due to unwanted inflammation, and microcirculation disruptions due to an ischemic result.…”
Section: Discussionmentioning
confidence: 99%
“…DFP shows a rather sudden onset, and it usually occurs more than 24 h after the operation [1]. Some authors have reported that the rate developing DFP following MVD is 2.8–8.3% [2,3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Among them, delayed facial palsy (DFP) reported most commonly. Several reports describe an incidence of DFP following MVD in HFS of 2.8-8.3%10,14,15,20). The purpose of this study was to evaluate the incidence of delayed cranial nerve (VI, VII, and VIII ) palsy following MVD and its clinical courses.…”
Section: Introductionmentioning
confidence: 97%